Agriculture and Agribusiness from the Perspective of al-Qur´an and al-Sunnah - Borhan, Joni Tamkin; Ab. Aziz., Muhammad Ridhwan (Jurnal Usuluddin, 2009)
This article examines the concept of agriculture and agribusiness from the spirit of al-Qur´an and al-Sunnah. Thus, this article will be divided into two sections. The first section begins with the exploration of agriculture, whilst the second section in this article will discuss the advantage of participating in agribusiness. The methodology of study in this article is mostly through the analysis of classical as well as modern sources regarding agriculture and agribusiness. Interpretation of verses of al-Qur´an and alSunnah are also included in the discussion of these topics. The finding shows that al-Qur´an and al-Sunnah give a clear message to the Muslim community that embarking in this sector is very important for producing food as a source of energy to the development of human body.